UMPSA launches Integrated TVET-Based Community Programme for Rumah Penyayang Tun Abdul Razak - Siti Nur Azwin, Zulkapri (UMPSA, 2025)
PEKAN, 4 July 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has taken a significant step in community empowerment by signing a Memorandum of Understanding (MoU) with Rumah Penyayang Tun Abdul Razak, aimed at supporting the underprivileged through education, skills training, technological empowerment, and overall well-being.